Green and chemical syntheses of silver nanoparticles: Comparative and comprehensive study on characterization, therapeutic potential, and cytotoxicity - Shivanjali Esther Arland; Jyotsna Kumar (Elsevier, 2024)
The emergence of metallic nanoparticles through green synthesis has garnered significant recognition, shaping global research efforts towards eco-friendly practices, often termed as the green revolution. Specifically, the green synthesis of silver nanoparticles (AgNPs) has made considerable strides in the past decade, becoming a prominent fixture in the realm of science and technology. The study explores the synthesis and characterization of silver nanoparticles (AgNPs) using Cassia fistula L. flowers extract through chemical co-precipitation (CM_AgNPs) and green methods (CFF_AgNPs). Characterization techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), attenuated total reflectance fourier-transform infrared (FTIR), and X-ray diffraction (XRD), revealed irregular morphologies with agglomeration, polycrystalline nature, and intrinsic functional groups involved in capping AgNPs. Antioxidant assessment demonstrated superior antioxidative activity (84.48 %) in green-synthesized nanoparticles compared to chemically synthesized ones (75.87 %), and they exhibited dose-dependent anti-inflammatory effects with IC50 values CFF_AgNPs_30.19 μg/mL and CM_AgNPs _34.14 μg/mL respectively. The lower IC50 value of CFF_AgNPs_30.19 μg/mL signifies finer and better activity due to the presence of phytochemicals present in it. Whereas for CM_AgNPs the IC50 value is a 34.14 μg/mL which is solely due to AgNPs. To ensure the promising therapeutic aspects of AgNPs with a careful assessment of their safety profile, cytotoxicity of AgNPs on HEP3B cancer cells was evaluated through MTT assay, lactate dehydrogenase (LDH) release, and reactive oxygen species (ROS) level measurement. In the in vitro cytotoxicity evaluation, HEP3B demonstrated more pronounced dose-dependent adverse effects upon exposure to CFF_AgNPs compared to CM_AgNPs. This study underscores the bioactive potential of Cassia fistula L. mediated AgNPs, suggesting promising applications in biomedicine with environmental sustainability. The findings contribute to the growing interest in green synthesis methods for metallic nanoparticles and their potential benefits in various fields.